2022
DOI: 10.1177/00037028221128800
|View full text |Cite
|
Sign up to set email alerts
|

Fluorometer Control and Readout Using an Arduino Nano 33 BLE Sense Board

Abstract: We describe the control and interfacing of a fluorometer designed for aerial drone-based measurements of chlorophyll- a using an Arduino Nano 33 BLE Sense board. This 64 MHz controller board provided suitable resolution and speed for analog-to-digital (ADC) conversion, processed data, handled communications via the Robot Operating System (ROS) and included a variety of built-in sensors that were used to monitor the fluorometer for vibration, acoustic noise, water leaks and overheating. The fluorometer was inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…As shown in another report from our laboratory, 31 the purely electronic instrumental noise was expected to be approximately 400 µV in 0.1 s measurement cycles from the manufacturer-reported input current noise specification for the system's transimpedance amplifier, leading to a model detection limit of 0.15 µg/L chl- a , approximately three times lower than the target specification (D.L. < 0.5 µg/L in 0.1 s) for the system.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…As shown in another report from our laboratory, 31 the purely electronic instrumental noise was expected to be approximately 400 µV in 0.1 s measurement cycles from the manufacturer-reported input current noise specification for the system's transimpedance amplifier, leading to a model detection limit of 0.15 µg/L chl- a , approximately three times lower than the target specification (D.L. < 0.5 µg/L in 0.1 s) for the system.…”
Section: Resultssupporting
confidence: 69%
“…Increasing detector size brings with it an increase in the detector's noise—but an analysis of the detection system done previously revealed that the detector itself would not be the dominant noise source in this fluorometer. 31 Tests conducted in the laboratory since the original construction have shown that the factor B 2 (0.407) could be increased to >0.92 by the expedient of replacing the final two spherical lenses with aspheres.…”
Section: Discussionmentioning
confidence: 99%
“…More detail on the electronic control, measurement, and communications of the fluorometer will be presented in a separate report. 22…”
Section: Methodsmentioning
confidence: 99%
“…More detail on the electronic control, measurement, and communications of the fluorometer will be presented in a separate report. 22 The fluorometer unit consisting of optics, hardware and electronics was constructed to fit into a waterproof case consisting of a 11.1 cm (4.375 in.) OD aluminum can with a length of 25.4 cm (10 in.).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the required instrumentation employed for fluorometric measurements has evolved in recent years from static designs mainly focused on laboratory assays towards more flexible, portable and handheld devices [10][11][12][13][14][15][16], which can be easily operated for in situ experiments. Thus, the increasing availability of the necessary components to build fluorometric detection devices, such as intense light sources with different excitation wavelengths (LEDs, fiber optic) [17,18] and compact micro-spectrometers for light analysis (C1280 MA) [19], and the existence of numerous computer-programmable microcontrollers (Raspberry Pi, Arduino) [20][21][22][23] allow the building of low-cost equipment [24][25][26] with unique features for in situ sample analysis with spectrofluorometric detection.…”
Section: Introductionmentioning
confidence: 99%